the Impact of Hemodialysis Combined with Hemoperfusion on Metabolism, Cytokines, and Novel Biomarkers in Chronic Kidney Disease Patients: Inflammation, Metabolism, and Biomarkers in CKD - Cai, Ming (Journal of Medical Biochemistry, 2026)
-
Keywords: HD; HP; CKD; metabolism; cytokines; oxidative stress; endothelial dysfunction; fibrosis; homocysteine; biomarkers